Trust management XI : 11th IFIP WG 11.11 International Conference, IFIPTM 2017, Gothenburg, Sweden, June 12-16, 2017, Proceedings /: 11th IFIP WG 11.11 International Conference, IFIPTM 2017, Gothenburg, Sweden, June 12-16, 2017, Proceedings. (2017) - Unknown
No abstract available